Hubungan antara perawatan payudara dengan kejadian bendungan asi (engorgement) pada ibu nifas - Tuti Meihartati (Jurnal Kebidanan dan Keperawatan Aisyiyah, 2017)
Abstract: The purpose of this study was to determine therelationship between breast care to the occurrence of engorgementat Poskesdes Sumber Baru Sub district Angsana Tanah BumbuRegency. The type of this research is analytic survey with crosssectional approach. The population in this study were allpostpartum mothers who experienced engorgement. The numberof samples were 63 respondents. Data analysis using chi-squaretest. The results of the study were 38 respondents. (66.3%) wererespondents who performed breast care, and 38 respondents(66.3%) did not have engorgement. Obtained a value of P 0.001that there is a relationship between breast care with the incidenceof engorgement. The conclusion that there is a relationship betweenbreast care with the occurrence of engorgement.